"Those who know don't tell": David Hammons c. 1981†. Issue 1 (2nd January 2019) - Schriber, Abbe
Abstract : Drawing on original archival research, as well as discourses in post-WWII art history, performance studies, and black studies, this article maps the use of rumor closely associated with David Hammons, with regard to two performative actions enacted in downtown Manhattan in 1981, now known as Pissed Off and Shoe Tree . These two performances occurred on and around the public sculpture T.W.U. (1980–81) by Richard Serra. Taking up how these works consider the specificity of social life pertaining to historically marginalized bodies and neighborhoods, this article argues that Hammons's work in this period employs obscurity as a resistance to knowledge as it is codified and legitimized in institutional discourses within and beyond art institutions.